(untitled) (Revista de História da UEG (REVHIST), 2019)
The following article analyses the relationship between Brazil and Portugal from 1964 to 1974, as well as the institutionalization of the powers of its authoritarian states. At that time, besides the particularities of each regime, Brazil and Portugal had similar predicates: anti communism as justification for the establishment of surveillance and authoritarianism as vector inhibitor of opposition and society controller. On one hand, the Portuguese Estado Novo sought to win Brazilian support to maintain its colonial empire in Africa. On the other hand, the civil-military dictatorship held a position consistent with the autonomy of people. This crossroad has become a flashpoint for Brazil-Portugal relations. It could be verified that many agreements, treaties, conventions, declarations, visits and cooperation were executed during the relationship between the two countries without the occurrence of divisions.